RELASI SOSIAL PETANI KOPRA DI KABUPATEN KEPULAUAN SELAYAR; STUDI PENDEKATAN ANALISIS GENDER - Nuryanti, Astiti; Sastrawaty, Nila; Anggaraini , Dewi (JURNAL SIPAKALEBBI, 2023)
This research aims to determine the system of division of labor among copra farmers and its impact on social relations on Kalaotoa Island, Pasilambena District, Selayar Islands Regency. This research uses descriptive qualitative research with a sociological approach. The data sources used in this research are primary data and secondary data, data collection used observation methods, interviews with 10 informants, and documentation studies. Techniques for managing and analyzing data are data reduction, data presentation, and drawing conclusions. The results of this research show that mapping the tasks of copra farmers on Kalaotoa Island, Pasilambena District, Selayar Islands Regency refers to the understanding that the processes in managing copra are based on physical strength. This work mapping does not have a significant influence on social relations between male workers and female workers. This can be seen, among other things, that male workers’ free time is not a problem because in certain situations male workers also help with female workers’ tasks. This is in line with Equilibrium Theory which emphasizes the concept of partnership and harmony between women and men.